Efektivitas Media Sosial Sebagai Media Promosi Kesehatan di Era Digital: Literatur Riview - Anggraini Siregar, Widya; Warda Situmorang, Fahita; Dewi Harahap, Rosmala; Nurhaliza Fardani, Siti; El Hayati, Miftahurrahmah (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2025)
The development of digital technology has brought significant changes in health promotion efforts. One form of its utilization is through social media which is considered effective in conveying health information widely and quickly. This study aims to assess the effectiveness of social media as a health promotion medium in the digital era. This study uses a literature review method by examining 15 relevant articles in the period 2015-2025 obtained through the Google Scholar database. The results of the study show that various social media platforms such as Instagram, Facebook, Twitter, YouTube, TikTok, WhatsApp, and blogs are used in various forms of health promotion. Social media is effective in increasing knowledge, health awareness, patient loyalty, and the number of visits to health facilities. In addition, social media is also effective in reaching adolescents in reproductive health education. However, the challenges faced include limited resources, changes in algorithms, ethical and privacy issues, and the risk of spreading invalid information. With proper management, social media has the potential to become an effective health promotion medium, with a wide reach, and is able to encourage changes in people's behavior towards a healthy life.